On the diagnostics of cerebral damage by nematodes - M. Yu. Chuchin (Лечащий Врач)
11 cases of cerebral nematodoses were observed in 2014–2017 years. In all cases of nematodosis specific radiological signs tunnel and visualization of helmint were registered; in 9 of 11 cases, previously unknown sing «clew in cross-section» was observed. This sign may be considered as specific for neuroimaging diagnosis of cerebral nematodosis.